Modeling the interaction between two-wheeled self-balancing vehicle and its rider - Ciężkowski, Maciej (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a modeling method and mathematical description of a two-wheeled self-balancing vehicle and its rider. A model of the rider that was used contains a model of the ankle joint, so we could determine the interaction between the rider and the vehicle. The paper presents results of computer simulations , which show the fundamental processes during riding, such as acceleration and braking.
Keywords: human-machine interaction; system control; ankle joint model; LQR; inverted pendulum